2020
DOI: 10.1049/hve.2019.0267
|View full text |Cite
|
Sign up to set email alerts
|

Charge accumulation characteristic on polymer insulator surface under AC voltage in air and C 4 F 7 N/CO 2 mixtures

Abstract: Charge accumulation has always been a problem for the safe operation of gas insulated switchgear (GIS)/gas insulated transmission line (GIL) both under AC and DC. It is of great significance to investigate the behaviour of surface charge under high voltage. In this study, the charge distribution characteristics and accumulation mechanism on insulator surface in air and heptafluorobutyronitrile/carbon dioxide (C 4 F 7 N/CO 2) mixtures under AC voltage are studied via the means of surface potential measurement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Charge transport behaviour is considered as an important issue related to electrical performances such as space charge accumulation, electrical treeing and dielectric breakdown [37][38][39]. The carrier traps in polymer have great impact on the charge transport, and are thought to be generated from physical defects (molecular weight distribution, free volume etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Charge transport behaviour is considered as an important issue related to electrical performances such as space charge accumulation, electrical treeing and dielectric breakdown [37][38][39]. The carrier traps in polymer have great impact on the charge transport, and are thought to be generated from physical defects (molecular weight distribution, free volume etc.)…”
Section: Discussionmentioning
confidence: 99%
“…The insulation performance of C3F7CN/CO2 gas mixture is more prominent, which may be due to the following reasons: 1) In terms of relative molecular weight, C3F7CN (195) is larger than SF6 (146), so the mobility of negative ions of C3F7CN molecules in the electric field is smaller. In addition, because the C3F7CN molecule has a larger collision cross section, the C3F7CN/CO2 mixed gas can effectively capture the electrons and ions generated after collision [24], thereby reducing the number of effective collision ionization and electron avalanches caused by electrons;…”
Section: B Effect Of Metal Particlementioning
confidence: 99%
“…Meanwhile, charge can accumulate on the insulator surface for long-term operation under the DC electric field [3][4][5][6][7][8]. The electric field generated by the surface charge can distort the initial field and possibly increase the risks of partial discharge or flashover [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that ion pairs generated in gas are the major source of charge accumulation on the insulator surface [9]. Cone-shaped insulators made of Al 2 O 3 -filled epoxy resin composites have been used to investigate the surface charge properties [4,5,10] and demonstrate the distortion of electric field distribution and the process of surface flashover [4]. Apart from the bulk effect of insulating materials, surface modification is utilized to generate more surface traps and suppress the charge accumulation [5,[10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation